Infografis Sebagai Media Sosialisasi untuk Meminimalisir Kebosanan Di Tempat Kerja - Rahmawati Syam; Syamsul Bakhri Gaffar; Novita Maulidya Jalal; St Hadjar Nurul Istiqamah; Dahlan Dahlan; Muh Alif Ulill Absar (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Boredom is a natural thing that happens to individuals in carrying out daily activities such as studying or doing difficult or monotonous work. Boredom can be defined as a condition in which the individual has low motivation and the task does not provide the desired stimulation. This program aims to provide information and knowledge in a simple and easy form to understand related to boredom. The benefit of this program is that readers, especially employees of the Telkom Witel Makassar, could easily understand the related topic, and could find solutions to reduce the level of boredom at work. The target of this program are employees of Telkom Witel Makassar and have read the author's infographic at least once. Initial data collection using observation, interview, and survey methods. Data collection for this program uses an evaluation of 13 Telkom employees involved in this program consisting of five men and eight women. Based on the evaluation, all of participants had felt bored at work. Repetitive work, excessive workload, and lack of motivation to work are the causes of perceived boredom. Participants can realize the causes of boredom and also know how to avoid boredom at work. All participants in this program feel that the information in the infographic is very useful for them.